Aerobic and Cognitive Exercise (ACE) Pilot Study for Older Adults: Executive Function Improves with Cognitive Challenge While Exergaming. (19th November 2015) - Barcelos, Nicole; Shah, Nikita; Cohen, Katherine; Hogan, Michael J.; Mulkerrin, Eamon; Arciero, Paul J.; Cohen, Brian D.; Kramer, Arthur F.; Anderson-Hanley, Cay
Abstract: Dementia cases are increasing worldwide; thus, investigators seek to identify interventions that might prevent or ameliorate cognitive decline in later life. Extensive research confirms the benefits of physical exercise for brain health, yet only a fraction of older adults exercise regularly. Interactive mental and physical exercise, as in aerobic exergaming, not only motivates, but has also been found to yield cognitive benefit above and beyond traditional exercise. This pilot study sought to investigate whether greater cognitive challenge while exergaming would yield differential outcomes in executive function and generalize to everyday functioning. Sixty-four community based older adults (mean age=82) were randomly assigned to pedal a stationary bike, while interactively engaging on-screen with: (1) a low cognitive demand task (bike tour), or (2) a high cognitive demand task (video game). Executive function (indices from Trails, Stroop and Digit Span) was assessed before and after a single-bout and 3-month exercise intervention. Significant group × time interactions were found after a single-bout (Color Trails) and after 3 months of exergaming (Stroop; among 20 adherents). Those in the high cognitive demand group performed better than those in the low cognitive dose condition. Everyday function improved across both exercise conditions. Pilot data indicate that for older adults, cognitive benefit while exergaming increased concomitantly with higher doses of interactive mental challenge. ( JINS, 2015, 21, 768–779)